CORPORATE TAX AVOIDANCE: A LITERATURE REVIEW AND RESEARCH AGENDA. (6th December 2019) - Wang, Fangjun; Xu, Shuolei; Sun, Junqin; Cullinan, Charles P.
Abstract: Tax avoidance can range from reduction of the corporate tax burden by legitimate use of tax rules to violation of tax laws. In this paper, we endeavor to synthesize the major findings of tax avoidance research from the accounting and finance literatures over the past ten years. We consider theoretical developments and the related empirical findings about the interconnected issues of measuring tax avoidance, and the possible causes and outcomes of corporate tax avoidance. We present some ideas for further research to examine underexplored topics regarding tax avoidance.